Unpacking stakeholder mechanisms to influence corporate social responsibility in the mining sector. (March 2017) - Viveros, Hector
Abstract: This paper examines mechanisms that stakeholder groups use in order to influence corporate social responsibility (CSR) and their involvement in the Chilean mining sector. The article adopts a qualitative approach and reports on semi-structured interviews conducted with five stakeholder groups. The findings show that the influence wielded by stakeholders to drive mining companies to act more responsibly is founded in five principal mechanisms: demands, communication, counselling, control and engagement. The manner in which stakeholders use these mechanisms varies across stakeholder groups. Some stakeholders adopt a single mechanism, as is the case for communities and media. Other stakeholders such as NGOs, adopt multiple mechanisms. From a dichotomised perspective in relation to involvement, the paper also identifies that stakeholders utilise these mechanisms considering an active (for groups such as government and media) and passive involvement (in the case of communities and unions). NGOs are the only stakeholder group that appear to adopt both active and passive participation, depending on the mechanisms under consideration. Highlights: The mechanisms are: demands, communication, counselling, control and engagement. A single mechanism is used by communities and media; NGOs adopt multiple mechanisms. Government and media are seen as active groups; communities and unions as passive. Stakeholder involvement varies depending on the mechanism employed.